Stress doesn’t kill us, it’s our reaction: exploring the relationship between coping mechanisms and correctional officer PTSD - Taylor, Katie Hughes (Promoting wellness and resiliency in correctional officers, 2023)
Developing research demonstrates that correctional officers (CO's) are at a higher risk for Post-Traumatic Stress Disorder (PTSD) than the general population, less is known about the relationship between how CO's cope with stress. Most CO's will be exposed to chronic stress and trauma while working in prisons, with approximately one-third of CO's eventually suffering from PTSD. It is important to explore the relationship between coping and PTSD because if certain coping styles are associated with different levels of PTSD, this could be used to inform training and programming for officers. This study examines officer coping and whether they impact the severity of PTSD symptoms among a group of approximately 245 correctional officers across seven adult state institutions from one Southern state. While controlling for exposure to violence and trauma experienced while on the job and adverse childhood experiences (ACEs), this study explores whether multiple problem-focused and emotion-focused coping mechanisms are associated with the level of PTSD symptoms experienced by CO's. Results indicated multiple problem- and emotion-focused coping mechanisms were significantly related to PTSD symptoms, even when controlling for exposure to violence and trauma, ACEs, and other controls. Implications these findings have for practice, and directions for future research are discussed.